Analyzing Discursive Constructions of Community in Newspaper Articles. Issue 3 (3rd November 2020) - Malherbe, Nick; Seedat, Mohamed; Suffla, Shahnaaz
Abstract: The manner by which power is reified through newspaper reporting can assist community psychologists in getting a handle on the complex, often contradictory, ways by which ideology and power are constituted in relation to particular communities. Accordingly, the present study draws on discursive psychology to analyse how 377 newspaper articles construct the community of Thembelihle (a low‐income community in South Africa) and how these constructions can inform counter‐hegemonic strategy. Two discourses were identified in the analysis, Signifying Legitimacy and Containing the Protest Community. Where the Signifying Legitimacy discourse established a Statist legitimacy‐illegitimacy binary against which Thembelihle was to be assessed, the Containing the Protest Community discourse constructed Thembelihle as a monolithic entity that enacted a wholly violent, and often directionless, mode of protest violence which was concerned with little more than 'service delivery'. Together, these discourses suggest to us the manner by which low‐income communities are engaged by the State as well as how Statist representations function materially. Certainly, most newspaper articles relied on an interpretive frame whose hermeneutics were characterised primarily by violence and homogenously experienced suffering. Such representation, we argue, signifies the dominant discursive field and ideology against which counter‐hegemonic strategy and (re)presentation must act. Highlights: Fleshes out a means of analyzing dominant discourse. Offers considerations for the development of counter‐hegemony. Demonstrates the use of critical media studies for community psychologists.